Comparison of concrete strength from cube and core records by bootstrap - Dauji, Saha; Bhargava, Kapilesh (Journal of Asian Concrete Federation, 2018)
In this article, non-parametric method of bootstrap is employed for estimation of the concrete properties such as mean, standard deviation and characteristic strength from core test results obtained from anexisting structure and then compared to those obtained from the original cube results, as reported in literature. Estimates obtained from Normal approximation theory are reported for comparison purposes. The slightly higher estimate of mean for the cores could be attributed to the gain in strength of concrete over the years due to progressive hydration of cement. There is large variation in the standard deviation between the original cube results and the present core results, the latter being higher. The estimated characteristic strength from the cubes and the cores varied marginally in either method of estimation, indicating that the present concrete quality on the structure is as good as the time of casting more than 25 years back. This could be attributed to the good quality control during casting and periodic maintenance for preserving the quality as was performed for the structure under examination.